The Diagnosis for The Preliminary Evaluation of The Development of Pedagogical Practice II 2025 For Physical Education and Sports Students - Pereira, Francisco Barbosa; Suzarte, Julio César Pérez; Martínez , Carlos Manuel Fuentes (CV. Green Publisher Indonesia, 2025)
Based on the importance of diagnosis as a systematic and continuous process of collecting, analyzing and evaluating information about the characteristics, needs, interests and potential of students and the educational context, in the present work a characterization of the behavior of the initial training of students of the curricular discipline Physical Education and Sports in Pedagogical Practice II is carried out, from the realization of class observations by the guiding professors. A sample of 18 students participate in the research, which constitute 56.25% of the population of the 3rd year of Physical Education and Sport. According to the objectives of this study, the research is based on a multiple case study, aiming to achieve a general and approximate understanding of the behavior of students in the development of Pedagogical Practice II. The research employs theoretical and empirical methods, using the appropriate techniques that are aligned with the established objectives and that address the research problem.